GE_GERICHTE P/13764/2017 vom 31. Oktober 2019 - GE Cour de justice (2019)
ACCIDENT DE LA CIRCULATION;FIXATION DE LA PEINE;FRAIS JUDICIAIRES | CP.125.al1; CPP.404.al1; CPP.433; CPP.426.al1; CPP.427; CPP.436; CP.34; CP.125.al1